2021
DOI: 10.1016/j.esxm.2021.100378
|View full text |Cite
|
Sign up to set email alerts
|

The Utilization and Impact of Aromatase Inhibitor Therapy in Men With Elevated Estradiol Levels on Testosterone Therapy

Abstract: Introduction: Testosterone therapy (TTH) for testosterone deficiency (TD) may lead to elevated estradiol (E2) levels requiring management to avoid unnecessary adverse effects. Aim: To examine the impact of aromatase inhibitors, specifically anastrozole (AZ), in men with elevated E2 on TTH.Methods: All patients on TTH at a high volume sexual medicine practice between 2005 and 2019 were reviewed. Men with E2 levels >60 pg/mL regardless of symptoms or 40−60 pg/mL with subjective symptoms were started on AZ 0.5 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The median pre-treatment E2 levels were 65 pg/mL vs. the 22 pg/mL post-treatment E2 levels. The testosterone levels did not show significant changes from pre-(616 ng/dL) to post-treatment (596 ng/dL) [56]. AIs are an effective way to control E2 levels during TRT.…”
Section: Ancillary Drugs During Trt To Maintain Fertilitymentioning
confidence: 81%
See 1 more Smart Citation
“…The median pre-treatment E2 levels were 65 pg/mL vs. the 22 pg/mL post-treatment E2 levels. The testosterone levels did not show significant changes from pre-(616 ng/dL) to post-treatment (596 ng/dL) [56]. AIs are an effective way to control E2 levels during TRT.…”
Section: Ancillary Drugs During Trt To Maintain Fertilitymentioning
confidence: 81%
“…AIs are mainly used to control elevated estradiol (E2) levels to prevent adverse effects in men on testosterone replacement therapy. One study examined the impact of anastrozole in men with elevated E2 levels due to testosterone therapy [56]. Patients with E2 levels of >60 pg/mL, regardless of the symptoms, or 40-60 pg/mL with subjective symptoms received 0.5 mg of anastrozole three times/week.…”
Section: Ancillary Drugs During Trt To Maintain Fertilitymentioning
confidence: 99%
“…Experimental animal studies have shown that the elimination of CYP19A1 in female mice significantly decreases estrogen levels and depression-like behavior ( Dalla et al, 2004 ). This may be related to the ability of CYP19A1 to convert T to E2 ( Punjani et al, 2021 ). In addition, the hippocampus is the critical lesion in depression.…”
Section: Introductionmentioning
confidence: 99%